2016
DOI: 10.1055/s-0035-1571199
|View full text |Cite
|
Sign up to set email alerts
|

A Worldwide Epidemic: The Problem and Challenges of Preterm Birth in Low- and Middle-Income Countries

Abstract: Preterm birth (PTB) is the most common cause of neonatal death worldwide and the second leading cause of under-5 mortality. Low- and middle-income countries (LMICs) bear a disproportionate burden of this disease. An estimated 1 million preterm infants die in the neonatal period each year and many of those who survive face lifelong disability. In this review, we explore the global burden of PTB through an examination of risk factors and predisposing clinical conditions found in LMICs. We then discuss current in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 136 publications
(169 reference statements)
0
20
1
Order By: Relevance
“…We think that preterm birth might mainly influence the growth of HEU children in the first 3 months, but sustained nutritional support over 18 months was the major factor influencing growth in these HEU children. We did not find an obviously higher rate of preterm birth among HEU children compared with previously reported rates of the general population [16, 17]. We also showed that both adjusted and unadjusted weight-for-age Z scores were slightly above zero from age 6 to 18 months, but that both adjusted and unadjusted length-for-age Z scores showed a decreasing trend to less than zero at age 18 months, which suggests that health interventions among HEU children in Guangdong Province are effective for weight but not length, or that HIV exposure might have a greater impact on length than on weight in HEU children.…”
Section: Discussioncontrasting
confidence: 98%
“…We think that preterm birth might mainly influence the growth of HEU children in the first 3 months, but sustained nutritional support over 18 months was the major factor influencing growth in these HEU children. We did not find an obviously higher rate of preterm birth among HEU children compared with previously reported rates of the general population [16, 17]. We also showed that both adjusted and unadjusted weight-for-age Z scores were slightly above zero from age 6 to 18 months, but that both adjusted and unadjusted length-for-age Z scores showed a decreasing trend to less than zero at age 18 months, which suggests that health interventions among HEU children in Guangdong Province are effective for weight but not length, or that HIV exposure might have a greater impact on length than on weight in HEU children.…”
Section: Discussioncontrasting
confidence: 98%
“…Preterm birth, the birth of a baby at fewer than 37 weeks of gestational age (128), is the most common cause of death among infants worldwide (129). Inflammation has been considered to be associated with preterm birth (130).…”
Section: The Roles Of Macrophages In Pregnancy Complicationsmentioning
confidence: 99%
“…Accurate estimates of PTB rates are necessary for resource allocation and to design appropriate interventions for the prevention and treatment of prematurity and its sequelae. However, in some settings (especially those where early ultrasonography is scarce and women present late to prenatal care), data are inadequate and national estimates must be modeled [1,2]. Nearly all obstetric studies performed in Africa, such as those that describe the effects of HIV and antiretroviral therapy on adverse birth outcomes, use definitions of gestational age based only on last menstrual period (LMP), symphysis–fundal height, and/or neonatal assessment [36].…”
Section: Introductionmentioning
confidence: 99%